Analisis Konsep Diri Dan Kedisiplinan Belajar Siswa MAN 1 Probolinggo Terhadap Matematika - Lestari, Wahyu; Hariyanti, Firda; Mauliska, Nur (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
Self-concept and learning discipline on student achievement play an important role, because self-concept and learning discipline can affect students' mathematical abilities. The purpose of this study is